TINJAUAN ETIKA BISNIS ISLAM TERKAIT PENGGUNAAN ALAT GANTI TIMBANGAN SEMBAKO (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2022)
This research intends to analyze the practice of using a tool to replace the scales in the selling and buying of groceries at the Cukir Diwek Jombang market, so that traders prioritize honesty and responsibility. This research uses an empirical juridical method by using an interview approach to find the object of research. The data will be presented descriptively-qualitatively. The result of this research is that some traders in Cukir Diwek Jombang are less concerned about the rules for replacing good scales in business ethics and some traders have implemented these Islamic business ethics. Keywords: Islamic Business Ethics, Scale Change Tool, Selling and Buying Transaction